METHODS OF TEACHER'S EDUCATIONAL WORK WITH YOUTH STUDENTS UNDER THE CONDITIONS OF MARITAL STATE - Маценко, Леся; Бричка, Ірина; Мельник, Альона (SWorldJournal, 2023)
The work examines the directions of the mentor's educational work with a student group in wartime conditions.